SCAFFOLDED READING EXPERIENCE (SRE) IN TEACHING READING COMPREHENSION - herawati unmura (STKIP PGRI Lubuklinggau, 2019)
The scaffolded reading experience framework consists of a set of prereading, during-reading, and post-reading activities to use with any genre of text, including fiction and nonfiction. The aim of this study was the effectiveness of scaffolded reading experience in teaching reading comprehension to the students of Musi Rawas University? The method used in this research was quasi-experimental method. The population of this study was all of the students of Musi Rawas University. The sample of this study was students of accounting study progrom in first semester taken through convenience non random sampling. The data were collected through a written test. It was pre-test and post test. The data analyzed through t-test formula. From this study it was found that the students’ pre-test average score in the experimental group was 55 and in the control group was 53.91. Meanwhile the students’ post-test average score in the experimental group was 80 and the students’ average score in the control group was 75. In addition of t-obtained were 2.049 where the value of t-table was 1.684 at df 74 in significance level of 0.05 and with one-tailed testing. Since the value of t-obtained was higher than the critical value of the t-table (2.049>1.684), it can be concluded that, teaching reading comprehension by using scaffolded reading experience (SRE) to the students of Musi Rawas University was effective.